2015
DOI: 10.17221/567/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Soil characteristics and crop yields under different tillage techniques

Abstract: The field experiment with different soil tillage treatments has been carried out in Prague-Ruzyně locality (Czech Republic) since 1995. Data of two growing cycles in the years 2007-2010 and 2011-2014 were evaluated. Tillage technique was decisive for changes in soil characteristics and crop yields. Bulk density, organic carbon (C org ) and microbial biomass C (C mic ) were more equilibrated throughout all tested soil layers (0-0.1; 0.1-0.2 and 0.2-0.3 m) in conventional tillage (CT). In reduced tillage (RT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The meteorological data; average and maximum daily temperatures ( • C) at 2 m and daily precipitation amounts (mm) is displayed in Figure 1. More detailed evaluation of basic soil characteristics of the top 30 cm together with microbiological analysis and crop yields for the experimental site can be found in a study presented by Mühlbachová et al [41].…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…The meteorological data; average and maximum daily temperatures ( • C) at 2 m and daily precipitation amounts (mm) is displayed in Figure 1. More detailed evaluation of basic soil characteristics of the top 30 cm together with microbiological analysis and crop yields for the experimental site can be found in a study presented by Mühlbachová et al [41].…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…RT protects the sub-soil against compaction and erosion by water, can also increase the stability of the soil through increased SOC (Czyż and Dexter, 2009). RT has effects on soil physical properties: bulk density, water content (Fabrizzi et al, 2005;McVay et al, 2006;Mühlbachová et al, 2015Pabin et al, 2003Sławiński et al, 2012), soil stability Dexter, 2008, 2009); chemical: SOC (Gajda et al, 2017(Gajda et al, , 2018Małecka et al, 2015;Mikanová et al, 2012), available forms of P, K and Mg (Franzluebbers, 2002;Małecka et al, 2015); and increased biological activity (Gajda et al, 2017) and diversity of diatoms (Stanek-Tarkowska and Noga 2012a,b;Stanek-Tarkowska et al, 2015) compared with TT. Czyż and Dexter (2009) reported that RT decreased the content of readily dispersible clay (RDC) and therefore increased soil stability.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of proper crop rotation and structure, and associated long-term changes in soil properties, are pointed out by Stehlíková et al (2015). Mühlbachová et al (2015) stresses new, soil-protecting tilling methods and their use.…”
mentioning
confidence: 99%